IMPLIKASI INVESTASI PERUSAHAAN MULTINASIONAL (MNC) ASAL EROPA TERHADAP LIFTING MIGAS INDONESIA TAHUN 2015-2019 - Salsa Melia Putri (2023)
This research is aimed at explaining the implications of European multinational company (MNC) investment for Indonesian oil and gas lifting activities in 2015-2019. MNC can channel its FDI into the Indonesian oil sector, because MNC sees the potential for Indonesia's petroleum reserves which are spread across various regions. Thus, Indonesia receives a significant amount of FDI in the country's petroleum sector from various foreign MNCs. The existence of this incoming FDI clearly presents various implications for the Indonesian oil sector to assist the government in increasing Indonesia's oil lifting results. However, the contribution from incoming foreign investment in the Indonesian petroleum sector is still insufficient to eliminate the gap between the target and the actual results of Indonesian oil lifting from 2015 to 2019. This is due to carrying out lifting activities, there are many factors that can affect the results the end of oil lifting activities carried out for example such as geological factors, technological factors, economic factors, and so on. So that the government made various efforts to encourage an increase in Indonesia's oil lifting results. The research was conducted using FDI theory and the concept of Natural Resource Management Policy. Then, the method used by the authors in this research is qualitative by collecting data through direct interviews with various parties or related agencies. The results of this study indicate that FDI provided by MNC companies from Europe contributes to the lifting of Indonesian oil.